Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1161/jaha.122.028866
|View full text |Cite
|
Sign up to set email alerts
|

Peptidase Inhibitor 16 Attenuates Left Ventricular Injury and Remodeling After Myocardial Infarction by Inhibiting the HDAC1‐Wnt3a‐β‐Catenin Signaling Axis

Abstract: Background Myocardial infarction (MI) is a cardiovascular disease with high morbidity and mortality. PI16 (peptidase inhibitor 16), as a secreted protein, is highly expressed in heart diseases such as heart failure. However, the functional role of PI16 in MI is unknown. This study aimed to investigate the role of PI16 after MI and its underlying mechanisms. Methods and Results PI16 levels after MI were measured by enzyme‐linked immunosorbent assay and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…We have noted also significant down-regulation of gelsolin (GSN), a known biomarker of rheumatic carditis, ficolin-3 (FCN3), which was also down-regulated in heart failure due to DCM or coronary heart disease, peptidase inhibitor 16 (PI16), known to be down-regulated in myocardial infarction and DCM, fibronectin (FN1), which is connected to coronary heart disease and DCM, or kallistatin (SERPINA4), which down-regulation in heart failure was connected to decreased survival time …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have noted also significant down-regulation of gelsolin (GSN), a known biomarker of rheumatic carditis, ficolin-3 (FCN3), which was also down-regulated in heart failure due to DCM or coronary heart disease, peptidase inhibitor 16 (PI16), known to be down-regulated in myocardial infarction and DCM, fibronectin (FN1), which is connected to coronary heart disease and DCM, or kallistatin (SERPINA4), which down-regulation in heart failure was connected to decreased survival time …”
Section: Discussionmentioning
confidence: 93%
“…43 Its reduced expression was observed in the heart tissues of DCM patients. 44 We have noted also significant down-regulation of gelsolin (GSN), a known biomarker of rheumatic carditis, 45 ficolin-3 (FCN3), which was also down-regulated in heart failure due to DCM or coronary heart disease, 46 peptidase inhibitor 16 (PI16), known to be down-regulated in myocardial infarction 47 and DCM, 41 fibronectin (FN1), which is connected to coronary heart disease 48 and DCM, 49 or kallistatin (SERPINA4), which down-regulation in heart failure was connected to decreased survival time. 50 To test the predictive value of DCM-associated proteins, we performed the logistic regression with elastic net optimization approach.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Pi16 was originally found to be a class of proteins of approximately 400 amino acids that can bind to PSP94 secreted in the blood of prostate cancer patients, located on human chromosome 6p21.2 5,6 . Subsequent studies have shown that Pi16 can also be secreted by myocardial fibroblasts and coronary endothelial cells and is found in cytoplasmic vesicles 23–25 . Interestingly, in addition to being a secreted protein, Pi16 also functions as a transmembrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that Pi16 is involved in a variety of pathophysiological processes and plays an important role in a variety of signaling pathways. Since Frost et al first discovered that Pi16 is highly expressed in cardiomyocytes, an increasing number of studies have confirmed that Pi16 not only participates in heart failure, myocardial hypertrophy, and myocardial infarction but also inhibits the inflammatory response of human coronary endothelial cells and cardiomyocyte fibrosis 24,25 . The role of Pi16 in tumors is also being explored.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of pi16 in recurrent prostate cancer has established its significance as a prognostic indicator, exhibiting a positive correlation with relapse-free survival [ 24 , 25 ]. Subsequently, PI16 was highly upregulated in cardiac disease and can inhibit the growth of cardiomyocytes [ 26 ] or attenuated left ventricular injury and remodeling after myocardial infarction [ 27 , 28 ]. In recent research, the function of PI16 in different organs and tissues is gradually being elucidated.…”
Section: Introductionmentioning
confidence: 99%